Kontribusi Muhammad Said Ramadhan al-Buthi dalam Studi Al-Qur'an - Irsyad, Muhammad; Alwis, Alwis (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
Ramadan al-Buthi is a popular, influential, controversial, unique scholar who has intensity and contribution. This library qualitative research discusses the contribution of Ramadhan al-Buthi in the study of the Koran. The results of the research revealed that Ramadhan al-Buthi is a multidisciplinary scholar who has become a reference in various fields of Islam. Among of the concentrations of his studies is the study of the Qur’an. The contribution of Ramadhan al-Buthi can be seen in his various works in the field of al-Qur’an studies both written and unwritten. In written form, it can be categorized into aspects: 1) the field of knowledge of the Qur’an, 2) doubts about the Qur’an, and 3) thematic Qur’an interpretation. Unwritten contributions in the form of seminars and recitations are one of the greatest, namely Tafsi>r al-Qur’a>n al-Kari>m in oral form which was recorded in 1000 episodes. Unfortunately, until now this interpretation has not been written down so knowledge regarding the methodology of the interpretation is still very limited.